2003
DOI: 10.1074/jbc.m303520200
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic PDZ Domain-mediated Protein Interactions Are Disrupted by Inhalational Anesthetics

Abstract: Anesthetics exert multiple effects on the central nervous system through altering synaptic transmission, but the mechanisms for this process are poorly understood. PDZ domain-mediated protein interactions play a central role in organizing signaling complexes around synaptic receptors for efficient signal transduction. We report here that clinically relevant concentrations of inhalational anesthetics dose-dependently and specifically inhibit the PDZ domain-mediated protein interaction between PSD-95 or PSD-93 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 56 publications
3
53
0
Order By: Relevance
“…PDZ domainmediated protein interactions play a central role in organizing signaling complexes around synaptic receptors for efficient signal transduction. Our previous studies have demonstrated that halothane dose-dependently and reversibly inhibits PSD-95 PDZ domain-mediated protein interactions and that the halothane binding site on PSD-95 PDZ2 completely overlaps with the binding pocket of PSD-95 for NMDAR NR2 subunits, 15 suggesting a new concept that affecting PDZ domain-mediated protein interactions at synapses in the CNS might be one of molecular mechanisms by which the general anesthetic state is achieved. By knocking down PSD-95 expression in the spinal cord, we have shown that the deficiency of spinal PSD-95 reduced isoflurane MAC in rats.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PDZ domainmediated protein interactions play a central role in organizing signaling complexes around synaptic receptors for efficient signal transduction. Our previous studies have demonstrated that halothane dose-dependently and reversibly inhibits PSD-95 PDZ domain-mediated protein interactions and that the halothane binding site on PSD-95 PDZ2 completely overlaps with the binding pocket of PSD-95 for NMDAR NR2 subunits, 15 suggesting a new concept that affecting PDZ domain-mediated protein interactions at synapses in the CNS might be one of molecular mechanisms by which the general anesthetic state is achieved. By knocking down PSD-95 expression in the spinal cord, we have shown that the deficiency of spinal PSD-95 reduced isoflurane MAC in rats.…”
Section: Discussionmentioning
confidence: 99%
“…14 Our previous studies have shown that clinically relevant concentrations of inhalational anesthetics dosedependently and specifically inhibit the PDZ domainmediated protein interaction between PSD-95 and NMDARs. 15 These inhibitory effects are immediate, potent, and reversible and occur at a hydrophobic peptide-binding groove on the surface of the PSD-95 PDZ2 in a manner relevant to anesthetic action. 15 These findings reveal the PDZ domain as a new molecular target for inhalational anesthetics.…”
Section: N-methyl-d-aspartate Receptor (Nmdar) Activationmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of anesthetics on the central nervous system is believed to alter synaptic transmission, but the molecular processes are poorly understood [10]. There is evidence that this action may result because of anesthetic-protein interactions [11].…”
Section: Anesthetic and Protein Interactionmentioning
confidence: 99%